A single crystal study of CPO-27 and UTSA-74 for nitric oxide storage and release. Issue 12 (15th February 2019) - Henkelis, Susan E.; Vornholt, Simon M.; Cordes, David B.; Slawin, Alexandra M. Z.; Wheatley, Paul S.; Morris, Russell E.
Abstract : Single crystal CPO-27-Mg, -Zn and its structural isomer UTSA-74 have been prepared through use of acid modulators; salicylic acid and benzoic acid, respectively. Abstract : Single crystal CPO-27-Mg, -Zn and its structural isomer UTSA-74 have been prepared through use of acid modulators; salicylic acid and benzoic acid, respectively. Salicylic acid directed the synthesis of CPO-27-Mg/Zn whereas benzoic acid the synthesis of UTSA-74. Through "in-house" SCXRD, DMF was seen to bind to the Zn 2+ and water to the Mg 2+ metal sites in CPO-27-M. Although the synthesis conditions were analogous for UTSA-74, DMF is too large to bind due to the proximity of the binding sites. A dissolution–recrystallisation transformation was examined from UTSA-74 to CPO-27-Zn. The release of nitric oxide was measured for each material.